Combined hormonal contraceptives as a risk factor for cerebrovascular accident - M. G. Novosartyan; N. V. Samburova; E. V. Anichkova; E. A. Bayanduryan; M. D. Andreeva; V. O. Bitsadze (IRBIS LLC, 2020)
Hormonal contraceptives are effective in preventing an unwanted pregnancy, but have side effects; among them stroke occupies an important place. The development of this serious disease may be associated with the hormonal drug components, but heavily dependent on additional risk factors for vascular and thrombotic complications such as smoking, arterial hypertension, genetically determined and acquired predisposition to thrombotic complications. This review presents an analysis of the most important risk factors for stroke such as genetic predisposition, hyperhomocysteinemia, thrombophilias in women using combined oral contraceptives.